Cell-free biodegradable electroactive scaffold for urinary bladder tissue regeneration - Rebecca L. Keate; Matthew I. Bury; Maria Mendez-Santos; Andres Gerena; Madeleine Goedegebuure; Jonathan Rivnay; Arun K. Sharma; Guillermo A. Ameer (Nature Communications)
Abstract Tissue engineering heavily relies on cell-seeded scaffolds to support the complex biological and mechanical requirements of a target organ. However, in addition to safety and efficacy, translation of tissue engineering technology will depend on manufacturability, affordability, and ease of adoption. Therefore, there is a need to develop scalable biomaterial scaffolds with sufficient bioactivity to eliminate the need for exogenous cell seeding. Herein, we describe implementation of an electroactive biodegradable elastomer for urinary bladder tissue engineering. To create an electrically conductive and mechanically robust scaffold to support bladder tissue regeneration, we develop a functionalization method wherein the hydrophobic conductive polymer poly(3,4-ethylenedioxythiophene) (PEDOT) is polymerized in situ within a similarly hydrophobic citrate-based elastomer poly(octamethylene-citrate-co-octanol) (POCO) film. We demonstrate the efficacy of this scaffold for bladder augmentation in primarily female athymic rats, comparing PEDOT-POCO scaffolds to mesenchymal stromal cell-seeded POCO scaffolds. PEDOT-POCO recovers bladder function and anatomical structure comparably to the cell-seeded POCO scaffolds and significantly better than non-cell-seeded POCO scaffolds. This manuscript reports a functionalization method that confers electroactivity to a biodegradable elastic scaffold, facilitating the successful restoration of anatomical and physiological function of an organ.